Locoregional peritoneal hyperthermia to enhance the effectiveness of chemotherapy in patients with peritoneal carcinomatosis: a simulation study comparing different locoregional heating systems. (1st January 2020) - Kok, H. Petra; Beck, Marcus; Löke, Daan R.; Helderman, Roxan F. C. P. A.; van Tienhoven, Geertjan; Ghadjar, Pirus; Wust, Peter; Crezee, Hans
Abstract: Introduction: Intravenous chemotherapy plus abdominal locoregional hyperthermia is explored as a noninvasive alternative to hyperthermic intraperitoneal chemotherapy (HIPEC) in treatment of peritoneal carcinomatosis (PC). First clinical results demonstrate feasibility, but survival data show mixed results and for pancreatic and gastric origin results are not better than expected for chemotherapy alone. In this study, computer simulations are performed to compare the effectiveness of peritoneal heating for five different locoregional heating systems. Methods: Simulations of peritoneal heating were performed for a phantom and two pancreatic cancer patients, using the Thermotron RF8, the AMC-4/ALBA-4D system, the BSD Sigma-60 and Sigma-Eye system, and the AMC-8 system. Specific absorption rate (SAR) distributions were optimized and evaluated. Next, to provide an indication of possible enhancement factors, the corresponding temperature distributions and thermal enhancement ratio (TER) of oxaliplatin were estimated. Results: Both phantom and patient simulations showed a relatively poor SAR coverage for the Thermotron RF8, a fairly good coverage for the AMC-4/ALBA-4D, Sigma-60, and Sigma-Eye systems, and the best and most homogeneous coverage for the AMC-8 system. In at least 50% of the peritoneum, 35–45 W/kg was predicted. Thermal simulations confirmed these favorable peritoneal heating properties of the AMC-8 system and TER values of ∼1.4–1.5 were predicted in at least 50% of the peritoneum. Conclusion: Locoregional peritoneal heating with the AMC-8 system yields more favorable heating patterns compared to other clinically used locoregional heating devices. Therefore, results of this study may promote the use of the AMC-8 system for locoregional hyperthermia in future multidisciplinary studies for treatment of PC.